Ultrasound features of arytenoid chondritis in Thoroughbred horses. (19th February 2013) - Garrett, K. S.; Embertson, R. M.; Woodie, J. B.; Cheetham, J.
Summary Reasons for performing study Laryngeal ultrasonography can provide valuable information when considering a diagnosis of arytenoid chondritis, but specific ultrasonographic parameters have not been defined. Objectives To compare ultrasonographic findings of the arytenoid cartilages in horses with endoscopically diagnosed arytenoid chondritis with ultrasonographic findings of the arytenoid cartilages in normal horses. Methods Ultrasound images of the larynx were obtained at the level of the arytenoid cartilages in horses with endoscopically diagnosed arytenoid chondritis and horses with normal arytenoid cartilage structure and function. Information obtained from the ultrasound examination included arytenoid cartilage cross‐sectional area, arytenoid cartilage echogenicity and arytenoid cartilage shape. Comparisons were performed between affected and unaffected arytenoid cartilages. For horses with multiple examinations, relationships between time point and arytenoid cartilage cross‐sectional area were determined. Results Chondritic arytenoid cartilages were significantly larger and had abnormal shape and echogenicity when compared with normal arytenoid cartilages (P<0.001). For horses with multiple examinations, no significant changes were identified in arytenoid cartilage size over time. Conclusions Chondritic arytenoid cartilages are increased in size and have abnormal echogenicity and contour in comparison with normal arytenoid cartilages when assessed using laryngeal ultrasonography. Once enlarged, the cartilage does not appear to return to normal size after the infection and/or inflammation has resolved. Potential relevance Ultrasonography is a valuable diagnostic modality when investigating cases of possible arytenoid chondritis or abnormal arytenoid cartilage movement. It has additional benefit in determining the extent of disease when medial masses are present on the surface of arytenoid cartilages, aiding in surgical decision making.